The Today Show: Transforming Morning Television - Londino, Cathleen M. (Rowman & Littlefield Publishers, 2016)
In the early 1950s, when television networks did not broadcast regular programming before 11 a.m., radio and newspapers were the most popular and reliable ways for Americans to get their morning news. Then, Sylvester (Pat) Weaver, vice president of programming at NBC, pitched a bold new concept to the network: a two-hour early morning news show that would run Monday through Friday starting at 7 a.m. By developing Today, Weaver filled a programming void before viewers even realized there was one—and revolutionized the viewing habits of millions. In The Today Show: Transforming Morning Television,Cathleen M. Londino provides an entertaining and informative look at the first twenty-five years of NBC’s innovative program, from 1952 through 1977. Focusing on Today’s broadcast history, the personalities instrumental to the show’s success, and the show’s contributions to the entertainment industry, this account illustrates how the evolution of Today closely paralleled the development of the broadcast industry and rise of the major networks. In addition to chronicling the show’s history, the author profiles some of the key players both behind and in front of the camera, including Dave Garroway, Barbara Walters, Tom Brokaw, and Jane Pauley. The vision of morning news developed by Weaver more than sixty years ago endured far beyond his wildest expectation, establishing a model that would eventually be adopted not only by competing networks but also by television programmers around the globe. The Today Show: Transforming Morning Television is a fascinating account of theunprecedented success of this influential program and will appeal to anyone interested in television history.